Thermal and Flow Behavior of Nanofluid over a Lubricated Stretching Sheet with Velocity Slip Effects (European Journal of Pure and Applied Mathematics, 2026)
This study presents a mathematical model for the two-dimensional flow of a nanofluid over a lubricated stretching sheet with a thin layer of power-law lubrication coating. A power-law lubricant layer of varying thickness coat the sheet, impacting the flow dynamics and heat transfer characteristics. Temperature-dependent thermal conductivity, Brownian diffusion, and thermophoresis effects are incorporated into modified governing equations corresponding to mass, momentum, energy, and concentration conservation laws. Key parameters affecting the thermal and solutal gradients in the nanofluid include the ambient and surface temperature, as well as concentration levels. The model accounts for both slip and no-slip boundary conditions due to the lubrication layer, and ensures interfacial shear stress continuity between the nanofluid and lubricant. Recently, heat transfer has been a noticeable enhanced due to nanoparticles interactions. The effect of lubrication phenomena and its impact on heat and mass transmission is crucial. The thermal effect of nanofluid on lubricated stretched surfaces close to a stagnation point has been investigated numerically in recent work. A reliable and effective method, the Keller Box Numerical Scheme, is used to solve the transformed ordinary differential equations in the boundary layer. Based on theoretical flow assumptions, a range of flow parameters is considered. When lubrication is applied, a physical analysis of relevant parameters, including temperature, concentrations, and velocity, is conducted. Slip conditions at the interface between the nanofluid and the power-law lubricant are enforced, incorporating surface slip and the stretching velocity of the sheet. Key parameters, such as the Brownian motion parameter, Prandtl number, Eckert number, and slip parameter are introduced to study the impact of fluid and thermal characteristics on the system.
Keywords: Lubricated stretching sheet, Power-law lubricant, Nanofluid flow, Energy transition, Brownian motion, Temperature-dependent conductivity, Slip conditions. Keller Box Scheme.